2019
DOI: 10.1038/s41598-019-44296-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolutionary responses to insecticide resistance management interventions by the German cockroach (Blattella germanica L.)

Abstract: The German cockroach ( Blattella germanica L.) is a worldwide pest that lives exclusively in human environments. B. germanica threatens human health by producing asthma-triggering allergens, vectoring pathogenic/antibiotic-resistant microbes, and by contributing to unhealthy indoor environments. While insecticides are essential for reducing cockroach populations and improving health outcomes, insecticide resistance has been a consistent barrier to cockroach control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 52 publications
0
40
0
1
Order By: Relevance
“…In the unicellular algae Chlamydomonas reinhardtii, selection with a herbicide mixture resulted in a broader, more generalist cross-resistance than selection with the mixture components individually 8 . In addition, attempts to control the cockroach Blattella germanica, using insecticide mixtures, were ineffective, and led to the rapid evolution of a generalist cross-resistance mechanism 54 . Together, these studies demonstrate that where generalist mechanisms of resistance exist, these may be preferentially selected through the use of mixtures and MOA diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In the unicellular algae Chlamydomonas reinhardtii, selection with a herbicide mixture resulted in a broader, more generalist cross-resistance than selection with the mixture components individually 8 . In addition, attempts to control the cockroach Blattella germanica, using insecticide mixtures, were ineffective, and led to the rapid evolution of a generalist cross-resistance mechanism 54 . Together, these studies demonstrate that where generalist mechanisms of resistance exist, these may be preferentially selected through the use of mixtures and MOA diversity.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments clearly highlight the relationships between the components of the temporal heterogeneity of fungicide selection and both resistance dynamics and the generalism or specialism of the evolved isolates. With this experimental design, we were able to validate, in a filamentous plant pathogen in vivo, the theoretical assumptions that temporal heterogeneity of selection can quantitatively modulate adaptation 13,20 and mediate generalism in evolved individuals 30,56 , as previously demonstrated for weeds, insects and bacteria 15,32,57,58,59,60 . Specifically, using three different fungicides, we found that alternation was either neutral or beneficial in terms of delaying global resistance, relative to the continuous use of a single fungicide, whatever its resistance risk.…”
Section: Discussionmentioning
confidence: 62%
“…Scanning our database of AKHs (see Gäde, ), Peram‐CAH‐I is not only found in the cucujiform beetles of the current study but has also been identified in blattid cockroaches, in some termites, some hemipteran bugs such as the water scorpion Laccotrephes fabricii (Nepidae; Gäde & Marco, ), the spittlebug Locris arithmetica (Cercopidae; Gäde & Marco, ) and the froghopper Ptyelus flavescens (Aphrophoridae; Gäde, Šimek, & Marco, ), as well as in very basal insects of the Archaeognatha (bristletails) and Zygentoma (firebrats) (Derst et al, ; Marco, Šimek, & Gäde, ). Not all of these listed species are considered serious pest insects, although it is demonstrated that blattid cockroaches not only have an increasingly strong negative impact on human health, but are also developing rapid resistance to all conventional insecticides (Fardisi, Gondhalekar, Ashbrook, & Scharf, ), and consequently, blattid cockroaches are certainly candidates for pest control. Unfortunately we do not have very much information of the AKH receptor in the aforementioned species that produce Peram‐CAH‐I, while the sequence of an AKH receptor is known from the blattid cockroaches P. americana and Blattella germanica (Hansen, Hauser, Cazzamali, Williamson, & Grimmelikhuijzen, ; Huang, Bellés, & Lee, ; Wicher et al, ), as well as that from the cucujiform beetle, the pine weevil H. abietis (Marchal et al, ).…”
Section: Resultsmentioning
confidence: 99%